2006
DOI: 10.1084/jem.20051921
|View full text |Cite
|
Sign up to set email alerts
|

Human mesenchymal stem cells exert potent antitumorigenic effects in a model of Kaposi's sarcoma

Abstract: Emerging evidence suggests that both human stem cells and mature stromal cells can play an important role in the development and growth of human malignancies. In contrast to these tumor-promoting properties, we observed that in an in vivo model of Kaposi's sarcoma (KS), intravenously (i.v.) injected human mesenchymal stem cells (MSCs) home to sites of tumorigenesis and potently inhibit tumor growth. We further show that human MSCs can inhibit the in vitro activation of the Akt protein kinase within some but no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
321
3
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 667 publications
(350 citation statements)
references
References 56 publications
17
321
3
3
Order By: Relevance
“…Additionally, it was suggested that engrafted MSCs also differentiated into colonic interstitial lineage cells and secreted vascular endothelial growth factor (VEGF) and transforming growth factor beta-1 (TGF-β1) those playing an important role in healing of injured colonic mucosa [41]. Supporting this observation, BMCs allograft to sites of Kaposi’s sarcoma potently inhibits tumor growth by down-regulating protein kinase B (AKT) activity in tumor cells [44]. Furthermore, cancer cells may produce proteins that can activate signaling pathways that facilitate and attract BMCs migration to the tumor site.…”
Section: Discussionmentioning
confidence: 72%
“…Additionally, it was suggested that engrafted MSCs also differentiated into colonic interstitial lineage cells and secreted vascular endothelial growth factor (VEGF) and transforming growth factor beta-1 (TGF-β1) those playing an important role in healing of injured colonic mucosa [41]. Supporting this observation, BMCs allograft to sites of Kaposi’s sarcoma potently inhibits tumor growth by down-regulating protein kinase B (AKT) activity in tumor cells [44]. Furthermore, cancer cells may produce proteins that can activate signaling pathways that facilitate and attract BMCs migration to the tumor site.…”
Section: Discussionmentioning
confidence: 72%
“…Therefore the introduction of a transgene into autologous stem cells possesses an attractive cell based delivery strategy [8,29]. On the contrary, other studies observed that MSCs may inhibit tumor growth in animal models [30,31] and posses antitumorigenic effects on a model of Kaposi's sarcoma [32].…”
Section: Discussionmentioning
confidence: 98%
“…Few contradictory reports appeared about spontaneous transformation of cultured bone marrow derived murine MSCs [32,33,34,35] and human MSCs [36,37]. It was reported that murine but not human mesenchymal stem cells generated osteosarcoma-like lesions in the lung [38].…”
Section: Discussionmentioning
confidence: 99%
“…While certain studies suggest that MSCs play tumor-suppressive roles (e.g., ref. 121 MSCs have also been shown to drive hematopoietic malignancies, such as multiple myeloma, 122,123 and appear to sustain leukemia/ lymphoma development. 124 Finally, MSCs have recently been found to promote the progression of certain mesenchymal cancers as well, such as osteosarcomas, which are thought themselves to arise, in part, from the neoplastic transformation of MSC lineages 34 (discussed in more detail below).…”
Section: Mscs In Tumor Pathogenesismentioning
confidence: 99%